2013
DOI: 10.1002/jwmg.510
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of voluntary mitigation in reducing harbor seal disturbance

Abstract: Marine and coastal tourism has rapidly expanded worldwide in the past 2 decades, often occurring in once secluded habitats. In Alaska, tourism near tidewater glaciers has attracted millions of visitors and increased the presence of ships, tour vessels, and coastal development. Although sustainable tourism, resulting from balanced effects on wildlife and client satisfaction, is a goal of most tourism operators, it is not always achieved. Voluntary compliance with viewing guidelines and codes of conduct have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…Observations were made from 27 May through 30 June 2001. entering the water increases with decreasing seal-vessel distance (Figs. 5 and 7)-a finding that agrees with those of other studies (Calambokidis et al 1 ;Jezierski, 2009;Jansen et al, 2010;Hoover-Miller et al, 2013, Young et al, 2014. However, seals in Tracy Arm during our study appeared to be less responsive to vessels at a given distance than seals in Disenchantment Bay, where only cruise ships were monitored (Jansen et al, 2010), and in Muir Inlet in GBNP where all vessel types were monitored (Calambokidis et al 1 ), and they were far less sensitive than seals in Johns Hopkins Inlet in GBNP (Young et al, 2014), even when accounting for vessel type.…”
Section: Vessels and Sealssupporting
confidence: 90%
See 4 more Smart Citations
“…Observations were made from 27 May through 30 June 2001. entering the water increases with decreasing seal-vessel distance (Figs. 5 and 7)-a finding that agrees with those of other studies (Calambokidis et al 1 ;Jezierski, 2009;Jansen et al, 2010;Hoover-Miller et al, 2013, Young et al, 2014. However, seals in Tracy Arm during our study appeared to be less responsive to vessels at a given distance than seals in Disenchantment Bay, where only cruise ships were monitored (Jansen et al, 2010), and in Muir Inlet in GBNP where all vessel types were monitored (Calambokidis et al 1 ), and they were far less sensitive than seals in Johns Hopkins Inlet in GBNP (Young et al, 2014), even when accounting for vessel type.…”
Section: Vessels and Sealssupporting
confidence: 90%
“…Some other studies had also noted that kayaks disturb seals at greater distances than those of motorized vessel types (e.g., power boats) (Jezierski, 2009;Hoover-Miller et al, 2013), but Calambokidis et al 1 found that harbor seals were equally sensitive to kayaks and tour boats (and less sensitive to pleasure boats [i.e., private vessels in our study]) and Young et al (2014) found seals were less sensitive to kayaks than any type of power vessel. It is possible that harbor seals can habituate to the noise of power boats and can determine a boat's approximate location by the sound of its engine.…”
Section: Odds Ratiomentioning
confidence: 99%
See 3 more Smart Citations